2011
DOI: 10.1111/j.1752-9824.2011.01079.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes type 2 self‐management among Thai Muslim women

Abstract: lundberg pc & thrakul s (2011) Journal of Nursing and Healthcare of Chronic Illness 3, 52–60
Diabetes type 2 self‐management among Thai Muslim women Aim.  To explore and describe Thai Muslim women’s self‐management of diabetes type 2. Background.  The importance of diabetes self‐management is well recognised. However, research on diabetes self‐management in Thailand is limited, and no such research related to Muslim patients with diabetes type 2 has been found. Methods.  An explorative qualitative study using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…The change of drug intake during Ramadan by several of the women is in accord with findings by several researchers (Aslam & Healy , Husain et al . , Bahammam , Lundberg & Thrakul 2011a). There is no medical agreement as to whether fast is safe for a person with diabetes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The change of drug intake during Ramadan by several of the women is in accord with findings by several researchers (Aslam & Healy , Husain et al . , Bahammam , Lundberg & Thrakul 2011a). There is no medical agreement as to whether fast is safe for a person with diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…Changes in meal frequency, daily physical activities and sleeping patterns during Ramadan may influence the glycaemia and other biochemical parameters in patients with diabetes. Although the Koran exempts sick people from fasting, many Muslims with diabetes do not perceive themselves as sick and choose to fast in opposition to medical advice (Husain et al 1987, Bahammam 2006, Lundberg & Thrakul 2011a. Naemiratch and Manderson (2006) found that individual explanations of control and adherence or resistance to medical advice are adapted in accord with Buddhist philosophy and Thai norms.…”
Section: Religion Spirituality and Diabetes Self-managementmentioning
confidence: 99%
“…2009). In Thailand, in particular, Muslim women with type 2 diabetes have been found to maintain Islam religious practices to cope with their disease (Lundberg & Thrakul 2010). Buddhism claims individual responsibility for fate, and illness is believed to result from a person’s past actions.…”
Section: Discussionmentioning
confidence: 99%
“…Family support, which helped the people with diabetes cope with their disease, is an important ingredient in the Thai culture, where the family has an important role in the provision of physical, mental and socio‐economic support to people with diabetes (Lundberg 2000, Lundberg & Rattanasuwan 2007, Lundberg & Thrakul 2010). This is in accord with Bai et al.…”
Section: Discussionmentioning
confidence: 99%
“…Many Asians, particularly those in mainly Muslim countries such as Indonesia, believe that health is a result of self-cultivation. Humans are created by God and how they treat themselves will influence their health condition (Lundberg & Thrakul, 2011). Providing information to people with diabetes on how to manage their disease would be more convincing to patients if health professionals related the information in a religious context.…”
Section: Content Of a Health Education Programmementioning
confidence: 99%